Lietuvos Didžiosios Kunigaikštystės rankraštinės knygos architektonika: vidinės sandaros raida - (:unkn) unknown (My University, 2013)
Straipsnyje analizuojama Lietuvos Didžiosios Kunigaikštystės (toliau – LDK) rankraštinės knygos architektonika ir jos raida nuo XIV a. iki XVI a. vidurio (t. y. iki 1569 m.). Didžiausias dėmesys skiriamas prasminei rankraštinės knygos struktūrai, kaip tiksliausiai atliepiančiai knygos suvokimą bei recepciją to meto visuomenėje ir paaiškinančiai tam tikrų knygos tipų susiformavimo ištakas LDK. Tyrimo metu nustatyti išskirtiniai knygos vidinės struktūros požymiai bei abipusė spausdintos ir rašytinės knygos sąveika, turėjusi įtakos tiek repertuarui, tiek dekorui.

A book consists of various interrelated external and internal elements, whose entirety is defined in book science by the term ‘architectonics’. A study of the development of book structure elements might be instrumental in finding out the depth of book culture reception in the Grand Duchy of Lithuania (GDL). The aim of this article is to analyze the development of the architectonics of the GDL manuscript book from the 14th to the mid-16th century (i. e. to 1569). To meet this aim, a task was undertaken to disclose the internal structure of the GDL manuscript book and its change until the mid-16th century and to determine specific features of this structure. The object of the study were 180 manuscript books written, copied or compiled in the GDL. The most attention has been accorded to the essential structure of the manuscript book as the characteristic that most precisely corresponds to the perception and reception of books in the then society and explains the reasons for the formation of certain types of books in the GDL. The present article analyzes main internal elements of a book: text field, main and auxiliary texts, decoration and illustrations. It has been determined that the GDL manuscript book in the studied period became an integral organism – with internal and external structure elements adapted for each book type and characterized by established hierarchy. Unusually wide text fields and neobyzantine decoration influenced by Western European art may be considered as distinctive features of the internal structure. In the early 16th century, in the GDL’s society, codex came to be viewed as an integral unit in respect of both form and contents (structure). A new phenomenon that emerged during this time – the mutual interaction of the printed and manuscript book – affected not only book repertoire, but also book decoration. The art of manuscript book-making reached a correspondingly high level so as to satisfy the increased requirements of various customers (both churchmen and laity).
The architectonics of the manuscript book of the Grand Duchy of Lithuania: the development of internal structure
Skyriaus antraštė: Moksliniai straipsniai